BASIC AND CLINICAL STUDIES ON RU 28965 - TOHGOH, TOSHITO; AMAGAI, RIEKO; HONMA, SATOKI; TOYODA, TAKEO; OKUI, SHINJI; FUJITA, TAKANORI; KAWAI, MIEKO; TAKASHI, KOHTARO; KURISHIMA, SETSUKO; YUHARA, TAKAMICHI; FUKUI, TOSHIO; KATSU, MASATAKA; et al. (CHEMOTHERAPY, 1988)
We examined RU 28965, a new macrolide for oral use, for its antibacterial activity in vitro and clinical efficac, and obtained the following results. 1. Antibacterial activity: MICs of RU 28965 for clinically isolated organisms were determined and compared with those of EM, MOM, JM, ABPC, and CCL. RU 28965 was most active against S. pyogenes, S. agalactiae and S. pneumuoniae, as were EM and ABPC. RU 28965 was a little less active against S. epidermidis, S. saprophyticus and H. influenzae than EM, but was more active against these than JM and MOM. Against S. aureus and C. jejuni, RU 28965 was a little less active than EM, JM and MOM. 2. Clinical efficacy A daily dose of 300 mg of RU 28965 was given orally for 3-14 days to 13 patients with respiratory tract infection. Clinical response was excellent in 1, good in 7, poor in 3 and unknown in 3 patients. As side-effects, eruption and diarrhea were observed in 1 patient. No abnormal laboratory findings related to RU 28965 were seen.